Direct measurement of enhanced electrocaloric effect in Mn2+ doped lead-free Ba(ZrTi)O3 ceramics. (February 2020) - Li, Hao-Xuan; Jian, Xiao-Dong; Niu, Xiang; Yao, Ying-Bang; Tao, Tao; Liang, Bo; Lu, Sheng-Guo
Abstract: The manganese doped barium zirconate titanate ceramics (Ba(Zr x Mn y Ti1- x - y )O3 -BZMT) ceramics with x  = 0.15, 0.20 and y  = 0, 0.0025, 0.0050, 0.0075, 0.0100, 0.0250, 0.0500 were prepared using an oxide reaction approach. The adiabatic temperature change was measured directly. Results revealed that by adjusting the nonequivalent Mn 2+ ionic concentration within 0.25–0.75%, desired dielectric performances with high permittivities and lower losses were obtained. The polarization was increased with the doping content of Mn 2+ ions. The largest electrocaloric temperature change obtained is 2.35 K for Ba(Zr0.15 Mn0.0025 Ti0.8475 )O3 ceramics at 62  °C, and a broad temperature range of ∼40  °C was accompanied. Graphical abstract: Image, graphical abstract